Birthplace diversity of the workforce and productivity spill-overs in firms - Karin Mayr; Rene Böheim; Thomas Horvath (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We analyze the effect of workforce composition by birthplace on workers' wages. In our model, each worker's productivity may depend on whether co-workers are of the same or of a different birthplace. Wages depend both on the relative size of workers' groups as well as on the production structure of firms. We derive empirically testable hypotheses about the effect of co-worker birthplace on wages using a stylized model of intra-firm spill-overs across worker groups. We find evidence for complementarities between workers of different birthplace in line with our model.
Keywords: D21; F22; J31; 330